Fire behavior of flame retarded sandwich structures containing PET foam cores and epoxy face sheets. Issue 12 (21st August 2020) - Bethke, Christian; Weber, Lais; Goedderz, Daniela; Standau, Tobias; Döring, Manfred; Altstädt, Volker
Abstract: Within this work, the investigation on interactions of a phosphorus‐containing flame retardant (FR) DEPAl in epoxy face sheets and five different FRs in the PET‐foam core of a sandwich laminate on the fire behavior is focused. Fourteen different combinations of resin face sheets and PET foam cores are produced by vacuum assisted resin infusion (VARI). The combustion behavior of the sandwich laminates is tested by cone calorimetry. The time to ignition is lowered when a FR resin is used while the subsequent burning behavior is mainly influenced by the PET foam core. In order to evaluate the interactions of the flame retardants in the core and face sheet, a total improvement value (TIV) was set up which compares the performance related to the specific FR combinations. The highest TIV value (76%) indicating positive interactions with DEPAl was observed with a 2‐PSMP‐PET core, the lowest value (−2%) with a DEPZn‐PET core. Abstract : Most flame‐retardant research focus on neat materials, such as PET and epoxy, only. Epoxy‐GF‐PET sandwiches made by VARI with different combinations of flame retardants in epoxy face sheet and PET core are investigated by cone calorimetry. Thereby, the influence on the burning behavior of 14 differently combined sandwich materials is investigated with regards to combined or synergistic effects.